A nondestructive study of the identification of pigments on monuments by colorimetry. (18th September 2009) - Cheilakou, E.; Kartsonaki, M.; Koui, M.; Callet, P.
The aim of this work was the identification of the pigments of the Philippe Dagobert monument (1222-1232) by spectrophotometry (Visible (VIS) region). Based on the bibliographic information about the pigments used in the Middle Ages, reference coloured samples were prepared in the laboratory. The study was based on the comparative analysis of VIS reflectance spectra, corresponding to laboratory measurements, with the in situ measurements. The obtained results allowed a primary identification of the pigments: the blue stimuli came from a mixture of azurite and malachite, the green from a mixture of equal concentrations of malachite and green earth, while the red and yellow were obtained from red and yellow ochre, respectively, presenting signs of ageing. Finally, it was concluded from these measurements that VIS reflectance spectroscopy could be considered an appropriate nondestructive method for the investigation and characterisation of the chromatic identity of monuments when no sampling is allowed.